Bentonit Clay Sebagai Bahan Untuk Bleaching Agent - Djumarman Djumarman (Balai Besar Kimia dan Kemasan, 1977)
Bleaching is the process of whitening a substance, in: the sense of making it more nearly white.Bleaching by absorption is often referred to as discolorization, Clay materials are widely used to discolorize,A variety of clay materials have been used for decolorization. One of them is bentonite clay